Spring-back simulation of unidirectional carbon/epoxy L- shaped laminate composites manufactured through autoclave processing - M. Nasir, M. Nazreen; Mezeix, Laurent; Aminanda, Yulfian; Seman, Adam; Rivai, Ahmad; Ali, Karim Mansur (IOP Publishing, 2016)
This paper presents an original method in predicting the spring-back for composite aircraft structures using non-linear Finite Element Analysis (FEA) and is an extension of the previous accompanying study on flat geometry samples. Firstly, unidirectional prepreg lay-up samples are fabricated on moulds with different corner angles (30o, 45o and 90o) and the effect on spring-back deformation are observed. Then, the FEA model that was developed in the previous study on flat samples is utilized. The model maintains the physical mechanisms of spring-back such as ply stretching and tool-part interface properties with the additional mechanism in the corner effect and geometrical changes in the tool, part and the tool-part interface components. The comparative study between the experimental data and FEA results show that the FEA model predicts adequately the spring-back deformation within the range of corner angle tested.